Gut microbiome affects the metabolism of metronidazole in mice through regulation of hepatic cytochromes P450 expression - Zemanová, Nina; Lněničková, Kateřina; Vavrečková, Markéta; Anzenbacherová, Eva; Anzenbacher, Pavel; Zapletalová, Iveta; Hermanová, Petra; Hudcovic, Tomáš; Kozáková, Hana; Jourová, Lenka (PLoS One, 2021)
Microbiome is now considered as a significant metabolic organ with an immense potential to influence overall human health. A number of diseases that are associated with pharmacotherapy interventions was linked with altered gut microbiota. Moreover, it has been reported earlier that gut microbiome modulates the fate of more than 30 commonly used drugs and, vice versa, drugs have been shown to affect the composition of the gut microbiome. The molecular mechanisms of this mutual relationship, however, remain mostly elusive. Recent studies indicate an indirect effect of the gut microbiome through its metabolites on the expression of biotransformation enzymes in the liver. The aim of this study was to analyse the effect of gut microbiome on the fate of metronidazole in the mice through modulation of system of drug metabolizing enzymes, namely by alteration of the expression and activity of selected cytochromes P450 (CYPs). To assess the influence of gut microbiome, germ-free mice (GF) in comparison to control specific-pathogen-free (SPF) mice were used. First, it has been found that the absence of microbiota significantly affected plasma concentration of metronidazole, resulting in higher levels (by 30%) of the parent drug in murine plasma of GF mice. Further, the significant interaction between presence/absence of the gut microbiome and effect of metronidazole application, which together influence mRNA expression of CAR, PPARα, Cyp2b10 and Cyp2c38 was determined. Administration of metronidazole itself influenced significantly mRNA expression of Cyp1a2, Cyp2b10, Cyp2c38 and Cyp2d22. Finally, GF mice have shown lower level of enzyme activity of CYP2A and CYP3A than their SPF counterparts. The results hence have shown that, beside direct bacterial metabolism, different expression and enzyme activity of hepatic CYPs in the presence/absence of gut microbiota may be responsible for the altered metronidazole metabolism.
Keywords: Liver; metronidazol; Animals; Gastrointestinal Microbiome; střevní mikroflóra; Mice; játra; Metronidazole; myši; zvířata